The Legal, Policy and Institutional Framework of Land Governance in Uganda: A Critical Analysis - Nakayi, Rose; Twesiime-Kirya, Monica (Human Rights and Peace Centre., 2017)
Land rights, access and ownership are among the most controversial and volatile issues facing the country today. They are simultaneously personal and political, social and economic, legal and administrative. Probably more than any other issue, land rights encapsulate the struggles and contestations around Ugandan national identity, gender relations, social status, class struggles and the governance system. Since colonial times, land has always been at the heart of politics in Uganda. Unfortunately, no government has yet been able to craft a lasting solution to the competing interests over land. Several factors have led to an escalation in the confl icts over land, among them a rising population, increased economic production and an increase in the value of land. These factors have made the issue of land justice more pertinent than it has ever been at any time in Uganda’s history. Those who have stood to gain the most have been those with the political and economic muscle to acquire land and secure their rights, while the vulnerable and marginalised, such as women, indigenous groups and internally displaced persons (IDPs), have often found themselves destitute and landless.